The Impact of Trade Agreements on World Export Prices - Lisandra Flach; Fabian Gräf (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper uncovers new stylized facts on the relation between economic integration and world trade prices. Using export price data combined with data on 32 WTO (World Trade Organization) accessions by developing countries and hundreds of new PTAs (Preferential Trade Agreements), we show that a country's membership in trade agreements is associated with an increase in export prices of differentiated goods. For WTO, this effect is captured by the developing countries that were subject to rigorous WTO accession procedures. We also exploit the importance of the depth of an PTA and of its different provisions. Whereas the effect of the depth per se is not significant, individual provisions evoke distinct effects on prices. In particular, we find that PTAs with provisions on investments are associated with higher export prices. The results are consistent with recent theoretical models that relate competition to the innovation behavior of firms.
Keywords: F13; F14; 330; export prices; WTO membership; PTAs; product quality